The role of respiratory function tests in infants with stridor: diagnosis at glance and follow-up - Silvia Bloise; Raffaella Nenna; Laura Petrarca; Maria Giulia Conti; Greta Di Mattia; Luigi Matera; Enrica Mancino; Domenico Paolo La Regina; Riccardo Lubrano; Enea Bonci; Corrado Moretti; Fabio Midulla (BMC, 2024)
Abstract Background Recently, the development of advanced, noninvasive methods has allowed the study of respiratory function even in uncooperative infants. To date, there is still little data on the application of this technique in infants with suspected airway obstruction. The aims of our study were: - To evaluate the role of respiratory function testing (PFR) in the diagnosis and follow-up of infants with stridor - To evaluate the differences between patients with inspiratory stridor and expiratory stridor. - To evaluate the concordance between PFR and endoscopy. Methods We enrolled infants aged < 1 year with a diagnosis of inspiratory and/or expiratory chronic stridor and a group of healthy controls. For each patient we performed PFR at diagnosis (T0) and for cases at follow-up, at 3 months (T1), 6 months (T2), 12 months (T3). At T0, all patients were classified according to a clinical score, and at follow-up, stature-ponderal growth was assessed. When clinically indicated, patients underwent bronchoscopy. Results We enrolled 48 cases (42 diagnosed with inspiratory stridor and 6 expiratory stridor) and 26 healthy controls. At T0, patients with stridor had increased inspiratory time (p < 0.0001) and expiratory time (p < 0.001) than healthy controls and abnormal curve morphology depending on the type of stridor. At T0, patients with expiratory stridor had a reduced Peak expiratory flow (p < 0.023) and a longer expiratory time (p < 0.004) than patients with inspiratory stridor. We showed an excellent concordance between PFR and endoscopic examination (k = 0.885, p < 0.0001). At follow-up, we showed a progressive increase of the respiratory parameters in line with the growth. Conclusions PFR could help improve the management of these patients through rapid and noninvasive diagnosis, careful monitoring, and early detection of those most at risk.